2020
DOI: 10.1111/iju.14403
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cancer therapy on post‐treatment ejaculation disorder and sexual life in testicular cancer survivors

Abstract: ObjectiveTo evaluate the impact of cancer therapy on post‐treatment ejaculation in patients with testicular cancer.MethodsA total of 74 testicular cancer survivors provided completed International Index of Erectile Function‐15 questionnaires before and after treatment between 2010 and 2017. Sexual function, particularly ejaculatory function, was evaluated before and after treatment. In this study, patients who answered “1 = almost never/never” or “2 = a few times” for questionnaire number 9 (ejaculation freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 30 publications
(36 reference statements)
2
11
1
Order By: Relevance
“…[14][15][16][17] However, treatment modality might have no obvious influence on erectile dysfunction, 16 consistent with our previous report. 10 In addition, we reported that ejaculation disorders occurred at a high rate following RPLND, and TC survivors after RPLND showed lower sexual QOL in a single-institutional study. 10 Recently, a multi-institutional, cross-sectional study was conducted to evaluate health-related QOL and fertility among TC survivors using the EORTC QLQ-TC26 in Japan.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…[14][15][16][17] However, treatment modality might have no obvious influence on erectile dysfunction, 16 consistent with our previous report. 10 In addition, we reported that ejaculation disorders occurred at a high rate following RPLND, and TC survivors after RPLND showed lower sexual QOL in a single-institutional study. 10 Recently, a multi-institutional, cross-sectional study was conducted to evaluate health-related QOL and fertility among TC survivors using the EORTC QLQ-TC26 in Japan.…”
Section: Introductionmentioning
confidence: 93%
“…10 In addition, we reported that ejaculation disorders occurred at a high rate following RPLND, and TC survivors after RPLND showed lower sexual QOL in a single-institutional study. 10 Recently, a multi-institutional, cross-sectional study was conducted to evaluate health-related QOL and fertility among TC survivors using the EORTC QLQ-TC26 in Japan. 12,[18][19][20] The EORTC QLQ-TC26 includes the questionnaire about sexual functioning; erectile and ejaculatory functions.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In a multivariate analysis, RPLND was an independent factor for EjD ( p = 0.042). They also used multivariate analysis to investigate the causative factors in 60 patients who stopped having sexual intercourse after treatment and found that the presence or absence of a partner and EjD were independent factors for the cessation of sexual intercourse (EjD odds ratio 14.8, 95% CI 1.21–181.26) 56 . EjDs after RPLND include retrograde ejaculation (RE) besides failure of emission; Hsaio et al examined the cause of postoperative EjD in 26 patients and found four patients with RE 57 .…”
Section: Sexual Dysfunction Of Cancer Survivorsmentioning
confidence: 99%
“…5 Recent evidence reported that ejaculatory dysfunctions (EjDs) occur at a high rate after retroperitoneal lymph node dissection, frequently performed in testicular and other pelvic cancers. 6 Moreover, EjDs are commonly associated with transurethral resection associated with an enlarged prostate and also represent significant side effects following the treatment lower urinary tract symptoms caused by prostate cancer. 7 To date, the main reviews and meta-analyses consider the association between specific cancer and EjDs and erectile dysfunction, but no comprehensive reviews exist on their prevalence.…”
mentioning
confidence: 99%